Glycoprotein Pathways Altered in Frontotemporal Dementia With Autoimmune Disease - Fiona Bright; Jared S. Katzeff; Jared S. Katzeff; John R. Hodges; John R. Hodges; Olivier Piguet; Olivier Piguet; Jillian J. Kril; Glenda M. Halliday; Glenda M. Halliday; Woojin Scott Kim; Woojin Scott Kim (Frontiers in Immunology, 2021)
Behavioral variant frontotemporal dementia (bvFTD) is a younger onset form of neurodegeneration initiated in the frontal and/or temporal lobes with a slow clinical onset but rapid progression. bvFTD is highly complex biologically with different pathological signatures and genetic variants that can exhibit a spectrum of overlapping clinical manifestations. Although the role of innate immunity has been extensively investigated in bvFTD, the involvement of adaptive immunity in bvFTD pathogenesis is poorly understood. We analyzed blood serum proteomics to identify proteins that are associated with autoimmune disease in bvFTD. Eleven proteins (increased: ATP5B, CALML5, COLEC11, FCGBP, PLEK, PLXND1; decreased: APOB, ATP8B1, FAM20C, LOXL3, TIMD4) were significantly altered in bvFTD with autoimmune disease compared to those without autoimmune disease. The majority of these proteins were enriched for glycoprotein-associated proteins and pathways, suggesting that the glycome is targeted in bvFTD with autoimmune disease.